Oral Tradition as a Source of Information on the Jacobean Pilgrimage Routes: the Example of Folk Songs and the English Way - Neira Pereira, Henrique (Madrygal. Revista de Estudios Gallegos, 2023)
The Galician folk songs that are still preserved in the oral tradition and that in many cases are already included in dozens of songbooks deal with very diverse topics. Among the most frequent are undoubtedly those that mention a city, a town or a locality, and within these there are many that relate them to a path that passes through there. There is also no lack of compositions with references to a town as a waypoint for Santiago, as a pilgrimage destination or simply as a destination for a trip –perhaps to go to a fair or a market–. Bringing together all the songs that we could find on the indicated topics and reviewing the origins of this lyrical modality, in this article we wanted to compile a small songbook about the Galician towns of the English Way and show its relevance as a source of information on the layout of the Jacobeans routes. It is not, therefore, a songbook exclusively about pilgrimages, but about the crossing points of the paths followed by the people who made the pilgrimage and the rest of the walkers who used them for any other reason
Keywords: Oral Tradition; Oral Literature; The Way of Santiago; The English Way